2016
DOI: 10.4017/gt.2016.15.3.005.00
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for enhancing success in digital tablet use by older adults: A pilot study

Abstract: Building on recent digital literacy initiatives, three strategies were identified for exploration, relating to successful use of digital tablets by older adults who lacked previous experience. The questions under investigation were: What are the implications of one-to-one support for self-efficacy and promoting attendance at digital literacy sessions? Could free tablets assist in overcoming economic and social barriers to participation? By what means could age-related physical problems with digital technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Martínez‐Alcalá et al (2018) demonstrated that not only can older adults benefit from digital literacy training, but also suggested a “blended workshop” platform by which this learning can be particularly effective. In a UK sample, Fletcher‐Watson et al (2016) demonstrated the acceptability and feasibility of a 6‐week training course in digital literacy aimed at older adults, finding almost 100% attendance throughout the course, and a large increase in reported self‐efficacy following the course. Similarly, recent work by Nicholson et al (2021) has demonstrated the effectiveness of a security training intervention designed at empowering older adults to provide support to peers in the community.…”
Section: Resultsmentioning
confidence: 99%
“…Martínez‐Alcalá et al (2018) demonstrated that not only can older adults benefit from digital literacy training, but also suggested a “blended workshop” platform by which this learning can be particularly effective. In a UK sample, Fletcher‐Watson et al (2016) demonstrated the acceptability and feasibility of a 6‐week training course in digital literacy aimed at older adults, finding almost 100% attendance throughout the course, and a large increase in reported self‐efficacy following the course. Similarly, recent work by Nicholson et al (2021) has demonstrated the effectiveness of a security training intervention designed at empowering older adults to provide support to peers in the community.…”
Section: Resultsmentioning
confidence: 99%
“…The study showed significant increases in post-intervention cognitive and delayed post-test knowledge scores, consistent with Tsai et al [ 23 ] and Jung and Park [ 24 ]. These findings suggest that virtual reality is an effective cognitive learning strategy, enhancing knowledge retention through observation, simulated operation, and repetition in a virtual environment [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, older adults may be less interested in learning how to use new technologies, and consider computers irrelevant to their everyday lives (Gatto & Tak, 2008;Wagner, Hassanein, & Head, 2010). Thirdly, age-related cognitive decline (e.g., working memory, attention) in older adults may reduce their ease of technology use (Fletcher-Watson, Crompton, Hutchison, & Lu, 2016), and cause difficulty when navigating and engaging with a system (Czaja et al, 2006;Hawthorn, 2000;Zajicek, 2004). Finally, it is common for older adults to become anxious around computers, and computer anxiety is an important predictor of computer use (Czaja et al, 2006;Yoon, Jang & Xie, 2016, Vaportzis, Giatsi Clausen & Gow, 2017).…”
Section: Introductionmentioning
confidence: 99%